Global Existence and Time-Decay Rates of Solutions to 2D Magneto-Micropolar Fluid Equations with Partial Viscosity (Journal of Partial Differential Equations, 2022)
In this paper, we investigate the initial value problem for the two-dimensional magneto-micropolar fluid equations with partial viscosity. We prove that global existence of smooth large solutions by the energy method. Furthermore, with aid of the Fourier splitting methods, optimal time-decay rates of global smooth large solutions are also established.
Keywords: Magneto-micropolar fluid equations with partial viscosity; global smooth large solutions; time-decay rates.